KECENDERUNGAN IMPULSE BUYING PADA MAHASISWA DITINJAU DARI LATAR BELAKANG KELUARGA - Exnasiyah Yahmini (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2019)
This research aimed to find out the impulsive buying tendency at college students from five universities in Yogyakarta and to discover the difference on the impulsive buying tendency at college students from five universities in Yogyakarta according to their family background including their parents status and occupations. This research used 100 respondents as the subject of this research. The data collection technique used in this research is Sampling Incidental technique. The instrument tests used in this research are validity and reliability test. The analysis technique used in this research is Independent Sample T-Test. The result of this research shows that the impulsive buying tendency at college students from five universities in Yogyakarta, based on their parents status, there is no different impulsive buying tendency between those who raised in two-parents family and single-parent family. Meanwhile, based on the parents occupations background, there is different impulsive buying tendency between those whose parentsoccupation is civil servant and those whose are not